2017
DOI: 10.1007/978-3-319-67035-5_7
|View full text |Cite
|
Sign up to set email alerts
|

On the Solution of Linear Programming Problems in the Age of Big Data

Abstract: The Big Data phenomenon has spawned large-scale linear programming problems. In many cases, these problems are non-stationary. In this paper, we describe a new scalable algorithm called NSLP for solving high-dimensional, non-stationary linear programming problems on modern cluster computing systems. The algorithm consists of two phases: Quest and Targeting. The Quest phase calculates a solution of the system of inequalities defining the constraint system of the linear programming problem under the condition of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
(19 reference statements)
0
23
0
Order By: Relevance
“…1) apply the Cimmino algorithm to implement the Qwest phase of the NSLP algorithm [2], designed to solve large-scale non-stationary linear programming problems;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) apply the Cimmino algorithm to implement the Qwest phase of the NSLP algorithm [2], designed to solve large-scale non-stationary linear programming problems;…”
Section: Resultsmentioning
confidence: 99%
“…As examples, we can mention linear programming [1,2], image reconstruction from projections [3], image processing in magnetic resonance imaging [4], intensity-modulated radiation therapy (IMRT) [5]. At the present time, a lot of methods for solving systems of linear inequalities are known, among which we can mark out a class of self-correcting iteration methods that allow efficient parallelization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quest phase calculates a point z belonging to the polytope M t . This phase is described in detail in [12]. The Quest Phase is followed by the Targeting phase.…”
Section: Nslp Algorithmmentioning
confidence: 99%
“…A distinctive feature of the Fejer process is its "self-guided" capability: the Fejer process automatically corrects its motion path according to the polytope position changes during the calculation of the pseudo-projection. The Quest phase was investigated in [12], where the convergence theorem was proved for the case when the polytope is translated with a fixed vector in the each unit of time. In the paper [17], the authors demonstrated that Intel Xeon Phi multi-core processors can be efficiently used for calculating the pseudo-projections.…”
Section: Introductionmentioning
confidence: 99%